2000
DOI: 10.1074/jbc.275.2.930
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine 5′-Phosphosulfate Sulfotransferase and Adenosine 5′-Phosphosulfate Reductase Are Identical Enzymes

Abstract: Adenosine 5-phosphosulfate (APS) sulfotransferase and APS reductase have been described as key enzymes of assimilatory sulfate reduction of plants catalyzing the reduction of APS to bound and free sulfite, respectively. APS sulfotransferase was purified to homogeneity from Lemna minor and compared with APS reductase previously obtained by functional complementation of a mutant strain of Escherichia coli with an Arabidopsis thaliana cDNA library. APS sulfotransferase was a homodimer with a monomer M r of 43,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 36 publications
1
74
0
3
Order By: Relevance
“…The enzyme produces sulfite from APS but not from PAPS, and the activity is stimulated by thioredoxin m but is not absolutely dependent on this compound. The reported V max of the Pseudomonas APR, 5.8 mol min Ϫ1 mg Ϫ1 (19), is almost identical to that of the N-domain of APR from Arabidopsis, 5.1 mol min Ϫ1 mg Ϫ1 , 2 being ϳ8 times lower than the V max of recombinant APR from Lemna minor (13). tive site, exactly like the enzyme from higher plants (14).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The enzyme produces sulfite from APS but not from PAPS, and the activity is stimulated by thioredoxin m but is not absolutely dependent on this compound. The reported V max of the Pseudomonas APR, 5.8 mol min Ϫ1 mg Ϫ1 (19), is almost identical to that of the N-domain of APR from Arabidopsis, 5.1 mol min Ϫ1 mg Ϫ1 , 2 being ϳ8 times lower than the V max of recombinant APR from Lemna minor (13). tive site, exactly like the enzyme from higher plants (14).…”
Section: Discussionmentioning
confidence: 63%
“…The plant APS reductase (APR), recently cloned from Arabidopsis thaliana, is a protein composed of two distinct domains: an N-terminal part is homologous to the Escherichia coli PAPS reductase (encoded by the cysH gene), and a C-terminal part is similar to thioredoxin with a function modified toward glutaredoxin (10 -12). This enzyme is identical to the previously described APS sulfotransferase (13) and contains a [4Fe-4S] iron-sulfur cluster as a cofactor (14). APS reductase is a highly regulated enzyme, and it is considered to have a major control on the flux through assimilatory sulfate reduction in plants (3,15).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Two catalytically distinct forms of ATP sulfurylase have been purified from Euglena gracilis, one of which exists in mitochondria (Li et al, 1991). APS reductase, formerly termed APS sulfotransferase (Suter et al, 2000), was found to be exclusively plastid-localized (Fankhauser and Brunold, 1978;Brunold and Suter, 1989;Rü egsegger and Brunold, 1993). In Euglena an isoform is also localized in mitochondria (Saidha et al, 1988).…”
Section: Cys Is Formed When Sulfide Reacts With O-acetyl Ser (Oas) Mementioning
confidence: 99%
“…In contrast, APS is used directly as the substrate for the reduction pathway. Reduced glutathione-dependent APS reductase (EC 1.8.99.-) transfers two electrons to form sulfite (Suter et al, 2000). Then ferredoxin-dependent sulfite reductase completes the reduction to sulfide.…”
mentioning
confidence: 99%